Top management team diversity, ambidextrous innovation and the mediating effect of top team decision-making processes. Issue 3 (2nd April 2016) - Li, Ci-Rong; Liu, Yan-Yan; Lin, Chen-Ju; Ma, Hong-Jia
Abstract: Until now, the amount of evidences for and discussions of how a top management team (TMT)'s composition influences ambidextrous innovation are very limited. This article develops and tests a model that connects task-related TMT diversity and TMT decision-making processes to explain the heterogeneity in a firm's strategic focus on ambidextrous innovation. The paper is based on a questionnaire survey/analysis with sample of 179 TMTs from high-tech firms in China. The conclusion exhibits that TMT task-related diversity has a strong effect on a firm's strategic focus on ambidextrous innovation through strategic decision-making activities. The findings suggest that the TMT debate and decision comprehensiveness can mediate the relationship between TMT task-related diversity and a firm's strategic focus on ambidextrous innovation. Overall, these results suggest that involvement in debate and comprehensiveness of strategic decision activities may bring out the potential of a TMT's diversity in enabling them to focus on ambidextrous innovation strategy.